PENGARUH SOCIAL MEDIA MARKETING MELALUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN LOKANATA COFFEE DI KOTA TASIKMALAYA - Tito Agustian, - (2022)
The objectives of this study: (1) To find overview social media marketing through instagram and purchasing decisions at Coffee Lokanata (2) To determine the effect of social media marketing on consumer purchasing decisions for Kopi Lokanata. The object of this research is Lokanata Coffee which is located on Jln AH Nasution No. 297b, Cipari, Mangkubumi, Tasikmalaya City. The method used is a quantitative method with descriptive and verification approach. In taking the sample using the slovin formula. Results Based on the research, the general category of good social media marketing with a percentage of 78.05%. The general description of purchasing decisions is in the good category with a percentage of 77.78%. The regression coefficient value is 0.776 so that the influence of social media marketing on consumer purchasing decisions for Lokanata Coffee is positive or influential. The social significance value of Media Marketing (X) is 0.001<0.1 and the value of tcount>ttable (9.867 > 1.661). It means that the significance value of social media marketing is 0.001 < 0.1 so that H1 is accepted and H0 is rejected. It can be concluded that there is significant influence between the Social Media Marketing variable (X) and the Purchase Decision variable (Y) partially accepted (Positive). The value of the coefficient of determination (R2) is found in the R Square value of 0.517. This means that the social media marketing ability variable in explaining the Purchase Decision variable is 0.517 or 51%. Calculation of data processing using SPSS version 28 program.